Pengaruh Konsentrasi Ragi Roti Terhadap Karakteristik Virgin Coconut Oil - Setia, Agung; Hendrawan, Hendrawan (Jurnal Dimamu, 2025)
Virgin Coconut Oil (VCO), or pure coconut oil, is obtained through a modified coconut oil production mechanism. This process aims to produce a product with very low water content, controlled free fatty acid levels, clear color, fragrant aroma, and the ability to last for more than a year. The purpose of this study was to determine how the concentration of baker's yeast (Saccharomyces cerevisiae) affects Virgin Coconut Oil (VCO). The method used was a randomized block design (RBD) with 6 treatments and 4 replicates. The VCO produced through fermentation with yeast concentrations of 0.5%, 0.8%, 1.1%, 1.4%, 1.7%, and 2% was analyzed for free fatty acid (FFA) content, moisture content, yield, and subjected to hedonic organoleptic testing (taste, aroma, color). The results showed that yeast concentration significantly affected ALB, yield, and organoleptic tests, but did not affect moisture content. Treatment with a yeast concentration of 0.5% produced VCO with the lowest ALB content (0.297%) and the highest hedonic scores for taste, aroma, and color. The highest VCO yield (20.72%) was obtained at a yeast concentration of 1.7%. Thus, a yeast concentration of 0.5% produced VCO with the best chemical and organoleptic quality, while a concentration of 1.7% provided the highest yield.